A Study on the Effects of Plastic Waste Strips and Lime on Strength Characteristics of Expansive Soil - Shelema Amena; Dekebi Chakeri (Advances in Civil Engineering)
Expansive soils are known for their volume changes due to fluctuation in the moisture content of the natural ground. This volume change causes huge destruction to many infrastructures. To avoid such damages, expansive soils should be well treated so that they become safe against bearing capacity failure and excessive settlement. In addition, everywhere plastic environmental pollution is a critical issue, which needs a proper way of utilization. This study primarily aimed at utilizing waste plastic materials with lime as subgrade pavement materials, which is cost-effective and environmentally friendly. Plastic water bottles are used as reinforcement with lime to improve the plasticity and strength properties of the expansive soils. Various laboratory tests are conducted using plastic waste strips with 0.25%, 0.5%, 0.75%, and 1% proportions as soil reinforcement and constant 5% of lime. Finally, significant improvements in CBR, unconfined compressive strength, and free swell are observed at 5% lime and 0.75% plastic waste strips. This study found that stabilizing expansive soil using plastic waste strips and lime has a great influence on the plasticity and strength parameters of the soil. This technique helps to reduce plastic pollution and minimize the cost of stabilizers used to stabilize the subgrade soil.